Conservative ideology in the U.S. Supreme Court in the 21st century - D.B. Makhambetsaliyev (Хабаршы. Заң сериясы, 2021)
At the beginning of the new millennium, the United States entered a new Republican Party cycle. The competition between the two leading parties in the 2000 elections was more acute than ever. It even resulted in a protracted constitutional and political crisis, when the U.S. Supreme Court had to stop the prolonged recounts in Florida (five votes in favor, four against), which was beneficial to the Republican parties. However, the Republicans managed to strengthen their future positions, and Democrat Barack Obama replaced Republican George W. Bush in the White House only after his two presidential terms. Should understand American constitutional judicial lawmaking primarily as the Supreme Court’s lawmaking as the activity of processing, interpreting, applying, and repealing regulations. Lawmaking activities aim to fill the gaps in legislation and reflect the objective needs of public life. Hence the importance of constitutional judicial lawmaking in human rights and other areas of legal regulation. As a legal tool, the U.S. Supreme Court uses procedural requirements and arguments in relatively (and specifically) undeveloped and unmodified legislation. The basis of constitutional lawmaking is the U.S. Supreme Court’s role in overseeing the implementation of judicial procedures. The requirement to comply with the procedural guarantees included in the U.S. Constitution’s text, which coincides with common law’s procedural requirements, is given the meaning of constitutional principles by the U.S. Supreme Court. Thus, there was no reason for conservatism’s full triumph in the early 21st century, as in the last decade of the 20th century. This celebration is not visible in the activities of the Supreme Court. Due to the death of W. Rehnquist in 2005, John Roberts, whose biography was very similar to Rehnquist’s in terms of close ties to the Washington bureaucracy, filled the Chairman’s vacancy. The Supreme Court of the United States in national minorities’ rights until the 2000s, despite the turn to constitutional judicial conservatism, did not move to a complete activism revision. The Court’s main goal was not to attack affirmative measures but to interpret state regulation’s doctrinal grounds, such as equal protection by law and due process. Still, conservative courts failed to change the role and reformat the meaning of doctrines.